ANTIOKSIDAN TANAMAN KOMODITAS HORTIKULTURA (HIAS) PADA EKSTRAK ETANOL 96% BUNGA ANGGREK BULAN (Phaeleonopsis amabilis L) DARI 3 LOKASI HASIL BUDIDAYA KULTUR JARINGAN (In Vitro) - Roni Gumilar; Firman Rezaldi; M. Fariz Fadillah; Andri Tri Cahyono; Tri Yudianto (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2022)
Currently, horticultural commodity plants that have been recorded consist of around 800 genera and 25,000 species, according to research, with approximately 800 genera and 25,000 species being orchids. Horticultural commodity plants, such as orchids, are species with high economic value that functionally serve as cut flowers as well as potted plants. The production of orchid flowers designed as horticultural commodities for cut flowers has increased in Indonesia by 8.99% from 2014 to 2015. The demand for orchids, particularly for the flowers, when viewed from the perspective of growth between 2014 and 2015, requires the production of quality seedlings to meet various needs, whether as ornamental plants, herbal medicine, or cosmetics. One of the methods that is fast, efficient, nutritionally controlled, free from pests and diseases, and genetically produces uniform plants with their parent is plant tissue culture. The tissue culture technique for plants is one of the solutions in the field of biotechnology to enhance plant species with high economic value, as well as to save plant species that are already threatened with extinction. The current condition of discoveries for producing new secondary metabolite compounds requires new sources of medicine, which have mostly shifted to orchid plants. This is due to the fact that the use of orchids has been widely utilized as ethnomedicine (herbal medicine) that is natural in nature. The secondary metabolites found in orchids certainly have pharmacological activity, one of which is as a source of antioxidants, compounds that can neutralize free radicals. This research aims to test orchid plants as a source of antioxidants from three cultivation locations of orchid plants derived from tissue culture (in vitro), namely the horticultural commodity plant laboratory in Pasir Banteng, Jatinangor, the orchid tissue culture laboratory in Serang, and the biotechnology orchid tissue culture laboratory at IPB. The research was conducted using the DPPH antioxidant activity method. The results of this study have demonstrated that each 96% ethanol extract from the three tissue culture cultivation locations has the potential to counteract free radicals, and the conclusion of this research, based on the IC50 value of the 96% ethanol extract of moon orchids cultivated from the biotechnology tissue culture laboratory at IPB, shows the best antioxidant value.